2012
DOI: 10.1099/jmm.0.042606-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of species-specific score cut-off values for various Staphylococcus species using a MALDI Biotyper-based identification

Abstract: Although previous studies investigating the MALDI Biotyper database (matrix-assisted laser desorption/ionization time-of-flight mass spectrometry-based identification) have proven its high accuracy for bacterial identification, the studies differed in sample preparation, number of replicates, quantity of shots and target types used. In particular, the score cut-off values of special importance for reliable species identification varied. The aim of the present study was to identify species-specific differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
(40 reference statements)
2
17
0
1
Order By: Relevance
“…Our previous experience in MALDI-TOF MS analyses suggested that the manufacturer-recommended confidence score thresholds for species might be overly conservative (Richter et al, 2012;Szabados et al, 2012). This was confirmed by reports on MALDI-TOF MS performed directly from positive blood cultures, as rates of concordance to species were similar using lower cut-off values compared to the manufacturer-recommended ones (Buchan et al, 2012;Christner et al, 2010;Klein et al, 2012;Lagace-Wiens et al, 2012;Prod'hom et al, 2010;Schubert et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our previous experience in MALDI-TOF MS analyses suggested that the manufacturer-recommended confidence score thresholds for species might be overly conservative (Richter et al, 2012;Szabados et al, 2012). This was confirmed by reports on MALDI-TOF MS performed directly from positive blood cultures, as rates of concordance to species were similar using lower cut-off values compared to the manufacturer-recommended ones (Buchan et al, 2012;Christner et al, 2010;Klein et al, 2012;Lagace-Wiens et al, 2012;Prod'hom et al, 2010;Schubert et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
“…Our prior studies indicated that the manufacturerrecommended MALDI-TOF MS confidence score thresholds for identification to the species level may be overly conservative (Richter et al, 2012;Szabados et al, 2012). Consequently, we applied different cut-off values for species identification (≥1.3 to ≥2.0) to the MALDI-TOF MS analyses performed for the 325 study isolates derived from monomicrobial blood cultures (Fig.…”
Section: Modification Of Maldi-tof Ms Confidence Score Cut-off Valuesmentioning
confidence: 99%
“…The manufacturer suggested a score ≥2.300 was needed for secure species identification, and 2.000-2.299 for secure genus but probable species identification. However, in practice, lower scores have been suggested as acceptable for species level identification (Richter et al 2012. For example, one study with ethanol/formic acid extraction suggested using scores of ≥2.0 for secure species identification of S. aureus, S.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study with ethanol/formic acid extraction suggested using scores of ≥2.0 for secure species identification of S. aureus, S. capitis, S. epidermidis, S. hominis, S. lugdunensis, S. saprophyticus, and S. simulans, and a score of 1.7 as sufficient for identification of S. caprae, S. sciuri, and S. cohnii (Richter et al 2012). This suggests that the species-specific score cutoff values may require additional optimization or more extensive representation in the database (Zhu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The relative ease of use, speed and cost effectiveness has generated substantial interest in the use of MALDI-TOF MS for identification of various microorganisms, including bacteria and fungi (Clark et al, 2013;Dubois et al, 2012;Szabados et al, 2012). While several reports have described the use of MALDI-TOF MS for the identification of Staphylococcus species, these studies have differed in sample preparation methods, diversity of species represented, number of replicates tested, reference identification methods, and interpretive criteria used (Clark et al, 2013;Dubois et al, 2010;Matsuda et al, 2012;Richter et al, 2012;Szabados et al, 2012).…”
Section: Introductionmentioning
confidence: 98%